The Clinimetric Properties of Instruments Measuring Home Hazards for Older People at Risk of Falling: A Systematic Review - Romli, Muhammad Hibatullah; Mackenzie, Lynette; Lovarini, Meryl; Tan, Maw Pin; Clemson, Lindy (SAGE Publications, 2018)
Home hazards are associated with falls among older people living in the community. However, evaluating home hazards is a complex process as environmental factors vary according to geography, culture, and architectural design. As a result, many health practitioners commonly use nonstandardized assessment methods that may lead to inaccurate findings. Thus, the aim of this systematic review was to identify standardized instruments for evaluating home hazards related to falls and evaluate the clinimetric properties of these instruments for use by health practitioners. A systematic search was conducted in the Medline, CINAHL, AgeLine, Web of Science databases, and the University of Sydney Library CrossSearch Engine. Study screening, assessment, and quality ratings were conducted independently. Thirty-six studies were identified describing 19 instruments and three assessment techniques. The clinimetric properties varied between instruments. The Home Falls and Accidents Screening Tool, Home Safety Self-Assessment Tool, In-Home Occupational Performance Evaluation, and Westmead Home Safety Assessment were the instruments with high potential for evaluating home hazards associated with falls. Health practitioners can choose the most appropriate instruments for their practice, as a range of standardized instruments with established clinimetric properties are available.